Permen Buah Karamunting: Inovasi Pangan Lokal untuk Penanggulangan Stunting pada Anak - Pereiz, Zimon; Oksal, Efriyana; Chuchita, Chuchita; Sylvani, Miranti Maya; Komara, Nisa Kartika (Yumary: Jurnal Pengabdian kepada Masyarakat, 2024)
Purpose: Stunting is a condition in which a child's physical growth and development are hampered due to malnutrition during the growth period. This condition occurs in children under 5 years of age. This age period is critical for the formation and development of body organs in children. Therefore, an innovative and holistic approach is needed to prevent stunting. One potential that can be exploited is the fruit of the karamunting plant (Rhodomyrtus tomentosa), which has traditionally been used as an herbal medicine. Candy containing healthy and delicious caramunting fruits can be an interesting way to increase nutritional intake, especially for children who have barriers to consuming nutritious food. Methodology: Implementation of community service through an educational workshop on the importance of knowledge about stunting prevention in children through local food innovation with Karamunting fruit candy (Rhodomyrtus tomentosa) was carried out on Saturday, October 7, 2023, between: 08.00-11.00 WIB, with the activity location at Habaring Hurung Village Hall. The partners for this community service activity are the heads and staff of Habaring Hurung Village, Bukit Batu District, Palangka Raya City, and Central Kalimantan. The targets of this service activity are mothers and children in Posyandu. Service procedures are the coordination, observation, activity implementation, and evaluation stages. Results: The participants understood the dangers and prevention of stunting in their children. The participants understood how to make karamunting fruit candy a local food that can be used and developed. Limitations: Karamunting fruit candy as a food innovation to prevent stunting produced by this community service program has no known expiration date or shelf life and there is no standard composition or dosage for candy to prevent stunting. Contribution: This community service activity can have a positive impact on the people of Hurung Village. This activity is able to increase insight and the ability to prevent the spread of stunting through innovation in making candy from karamunting fruit, even if residents can implement it independently.